2008
DOI: 10.1017/s1461145708008663
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 12-week open-label memantine treatment on cognitive function improvement in patients with alcohol-related dementia

Abstract: There is compelling evidence that alcohol-induced neurotoxicity is related to glutamate excitotoxicity. It was hypothesized that the low-affinity NMDA receptor antagonist memantine would improve the cognitive function of patients with alcoholic dementia. The aim of this study was to test this hypothesis and to evaluate the effect of memantine on the cognitive improvement of patients with alcohol-related dementia (ARD). The study was designed as a 12-wk open-label study investigating the efficacy of 20 mg meman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 63 publications
0
35
0
Order By: Relevance
“…A 12-week study on patients with probable ARD showed significant improvements on global cognition, quality of life and behavioral symptoms (76). Another memantine trial on WKS patients also showed improvement in cognition (word list recall, word list recognition, time orientation, drawing an interlocking pentagon and the total Mini Mental State Examination - Korean version) of all the patients (77).…”
Section: Resultsmentioning
confidence: 99%
“…A 12-week study on patients with probable ARD showed significant improvements on global cognition, quality of life and behavioral symptoms (76). Another memantine trial on WKS patients also showed improvement in cognition (word list recall, word list recognition, time orientation, drawing an interlocking pentagon and the total Mini Mental State Examination - Korean version) of all the patients (77).…”
Section: Resultsmentioning
confidence: 99%
“…Pathological gambling also demonstrates clinical and biological similarities with drug addictions (Holden, 2010; Potenza, 2006; Potenza, 2008). Consistently, treatments, particularly those with proposed mechanisms of action (e.g., modulation of neurotransmission in the meso-limbic dopamine pathway by opioid receptor antagonists like naltrexone or nalmefene or enhancing cognitive function via glutamatergic agents like memantine) that target features observed across addictions, appear efficacious for both substance and gambling addictions (Brewer et al, 2008b; Cheon et al, 2010; Grant et al, 2010a; Potenza, 2008). Furthermore, among individuals with pathological gambling, response to an opioid receptor antagonist appears strongly related to a family history of alcoholism (Grant et al, 2008), suggesting a possible endophenotype common to pathological gambling and alcoholism.…”
Section: Future Directions: Individual Differences Endophenotypes Amentioning
confidence: 97%
“…When thiamine-induced glutamate release is combined with ethanol-induced glutamate receptor up-regulation, the potential for excitotoxicity would be compounded. In anecdotal reports patients with Wernicke-Korsakoff syndrome have experienced symptomatic improvement following treatment with the glutamate NMDA receptor antagonist memantine [21,22]. (They have also reportedly improved after treatment with cholinergic agents such as donepezil and rivastigmine [23,24].…”
Section: Nutritional Deficiency Disordersmentioning
confidence: 99%
“…In an open label study of 19 patients with probable ethanol-related dementia, cognitive improvement followed treatment with the glutamate NMDA receptor antagonist memantine [21]. (As noted, Wernicke-Korsakoff syndrome also reportedly benefits from memantine therapy [22]. )…”
Section: Alcoholic Dementiamentioning
confidence: 99%